39 REGULATION OF SPHINGOSINE 1-PHOSPHATE-INDUCED ENDOTHELIAL CYTOSKELETAL REARRANGEMENT AND BARRIER ENHANCEMENT BY S1P1 RECEPTOR, CAVEOLIN-ENRICHED MICRODOMAINS, PI3 KINASE AND TIAM1/RAC1. (1st March 2005) - Singleton, P. A.; Garcia, J. G.N.
Abstract : Endothelial cell (EC) barrier dysfunction results in increased vascular permeability observed in inflammation, tumor angiogenesis and atherosclerosis. Sphingosine-1-phosphate (S1P) is a platelet-derived phospholipid which decreases EC permeability in vitro and in vivo with obvious potential as a therapeutic strategy. We examined S1P-mediated human pulmonary artery EC signaling and barrier regulation in caveolin-enriched microdomains (CEM). Immunoblotting from control or S1P-treated EC revealed S1P-mediated rapid recruitment (1 μM, 5 min) to CEMs of the S1P receptors, S1P1 and S1P3, p110 PI3 kinase α and β catalytic subunits (but not γ and δ) and the Rac1 guanine nucleotide exchange factor Tiam1. Immunoprecipitated p110 PI3 kinase catalytic subunits from S1P-treated EC exhibited evidence of kinase activity verified by PIP3 production in CEMs. Immunoprecipitation of S1P receptors from CEM fractions revealed complexes containing Tiam1 and S1P1 (but not S1P3). PI3 kinase inhibition (LY294002) attenuated S1P-induced Tiam1 association with S1P1, Tiam1/Rac1 activation and EC barrier enhancement. Finally, silencing of either S1P1 or Tiam1 expression resulted in the loss of S1P-mediated Rac1 activation, cortical F-actin rearrangement and S1P-mediated barrier enhancement. Taken together, these results suggest that S1P-induced recruitment of S1P1 to CEM fractions promotes PI3 kinase-mediated Tiam1/Rac1 activation required for cortical actin rearrangement and EC barrier enhancement.